Association between the CTLA4 +49A/G (rs231775) and CT60 (rs3087243) gene variants with vitiligo: study on a Mexican population - Mauricio Andrés Salinas-Santander; Víctor de Jesús Suárez-Valencia; Mayela del Ángel-Martínez; David Emmanuel Kubelis-Lopez; Natalia Aranza Zapata-Salazar; Jorge Alejandro Ocampo-Garza; Jorge Ocampo-Candiani (Sociedade Brasileira de Dermatologia, 2022)
Abstract Background: Vitiligo is characterized by an autoimmune response targeting melanocytes, thus resulting in skin depigmentation. There are several genetic components involved in the development of vitiligo, of which various gene polymorphisms are currently considered as risk factors. For example, the CTLA4 (T-lymphocyte antigen 4) +49A/G (rs231775) and CT60 (rs3087243) gene variants have been associated with a predisposition for autoimmune diseases in different populations; however, their involvement in the development of vitiligo remains controversial. Objective: We evaluated the association between vitiligo and the CTLA4 +49A/G (rs231775) and CT60 (rs3087243) gene variants in a Mexican population. Methods: A total of 116 vitiligo patients and 117 control subjects from northeast Mexico were included in the study and analyzed through PCR-RFLP to determine whether there is an association between vitiligo and CTLA4 +49A/G (rs231775) and CT60 (rs3087243) gene variants. Results: No statistical difference was observed for both gene polymorphisms between vitiligo patients and controls (p > 0.05). Otherwise, vitiligo activity, family history of vitiligo, personal history of autoimmune diseases, or sex did not show any difference (p > 0.05). Conclusion: As suggested by the analysis of a northeastern Mexican population, the CTLA4 +49A/G (rs231775) and CT60 (rs3087243) gene variants do not constitute a risk factor in the development of vitiligo.